The risk of vector transmission of Trypanosoma cruzi remains high in the State of Paraná. - Trovo JVS; Weber-Lima MM; Prado-Costa B; Iunklaus GF; Andrade AJ; Sobral-Souza T; Muylaert RL; Alvarenga LM; Toledo MJO (Instituto Oswaldo Cruz, Ministério da Saúde, 2024)
BACKGROUND: Monitoring and analysing the infection rates of the vector of Trypanosoma cruzi, that causes Chagas disease, helps assess the risk of transmission. OBJECTIVES: A study was carried out on triatomine in the State of Paraná, Brazil, between 2012 and 2021 and a comparison was made with a previous study. This was done to assess the risk of disease transmission. METHODS: Ecological niche models based on climate and landscape variables were developed to predict habitat suitability for the vectors as a proxy for risk of occurrence. FINDINGS: A total of 1,750 specimens of triatomines were recorded, of which six species were identified. The overall infection rate was 22.7%. The areas with the highest risk transmission of T. cruzi are consistent with previous predictions in municipalities. New data shows that climate models are more accurate than landscape models. This is likely because climate suitability was higher in the previous period. MAIN CONCLUSION: Regardless of uneven sampling and potential biases, risk remains high due to the wide presence of infected vectors and high environmental suitability for vector species throughout the state and, therefore, improvements in public policies aimed at wide dissemination of knowledge about the disease are recommended to ensure the State remains free of Chagas disease.
Keywords: Chagas Disease; Animals; Insect Vectors; Trypanosoma cruzi; Brazil; Triatominae; Humans; Risk Factors; Risk Assessment; Ecosystem